Order 53 of the Rules of Court 2012: An Analysis on Judicial Review (Kanun: Jurnal Undang-undang Malaysia, 2022)
The usage of the word "Allah" by non-Muslims is a controversial issue that was much-discussed in early 2021. This is because of the decision by the High Court of Malaya in the case of Jill Ireland bt Lawrence v Menteri Bagi Kementerian dalam Negeri Malaysia & Anor [2021] 8 MLJ 890 (Jill Ireland). This case has been publicly criticized as a result of the findings of the Court in judicial review by the applicant. The purpose of this research is to discuss how the High Court applied its jurisdiction in the judicial review in this case. In addition, the principles from this case are also compared with other cases in Malaysia concerning application of judicial review to obtain the principle for judicial review used in Malaysia. The researcher then compares this to the legal principle of judicial review in India. Since most of the sources are books and articles, the researcher employs a qualitative method in this research to discuss the issue in more depth. The researcher also studied case decisions. Data was also obtained using the library research method. The researcher provides an opinion on the issues discussed.Keywords: Word of "Allah", judicial review in Malaysia, judicial review in India, legal principle, validity, case decisionsFull text: PDF